New Developments in 4th generation district heating and smart energy systems - Østergaard, Poul Alberg; Johannsen, Rasmus Magni; Lund, Henrik; Mathiesen, Brian Vad (International Journal of Sustainable Energy Planning and Management, 2020)
This editorial introduces the 27th volume of the International Journal of Sustainable Energy Planning and Management, which reports some of the latest developments in energy systems analyses of smart energy systems as well as district heating. The issue looks into district heating in Estonia and Norway – as part in a renewable energy transition and flexibility-providing measure. Other analyses look into future prices of renewable energy-based power production systems and optimal design of carbon-neutral energy systems combing EnergyPLAN and EPLANOpt.